2008
DOI: 10.1111/j.1468-0297.2007.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Feature: The Price of Reconciliation: Part‐Time Work, Families and Women's Satisfaction

Abstract: While the gender pay gap has been narrowing for women in full-time jobs the pay penalty for the 40% of women who work part-time has risen, reflecting the growing polarisation of part-time jobs in low-wage occupations. A further dimension is that women often experience downgrading from higher-skill full-time into lower-skill part-time occupations. As women reorganise their working lives around the presence of children their reported hours and job satisfaction are highest in part-time work, but life-satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 2 publications
6
58
0
3
Order By: Relevance
“…Manning and Petrongola (2008) argue that, in the UK, females working part-time earn less than their full-time counterparts as they are more likely to be employed in jobs that tend to not be available on a full-time basis, suggesting that it is not always possible for a woman with family responsibilities to remain in their chosen occupation. Thus, the higher incidence of low pay among females may be due to the necessity of being forced to switch to lower-paid employment, in order to balance work and caring commitments (Gregory and Connolly, 2008). For the US, England et al (1999) found little evidence to support the view that occupations with disproportionately high shares of female workers had lower pay penalties for intermittent employment, which is consistent with a constrained choice argument.…”
Section: Chapter 1 Introductionsupporting
confidence: 61%
“…Manning and Petrongola (2008) argue that, in the UK, females working part-time earn less than their full-time counterparts as they are more likely to be employed in jobs that tend to not be available on a full-time basis, suggesting that it is not always possible for a woman with family responsibilities to remain in their chosen occupation. Thus, the higher incidence of low pay among females may be due to the necessity of being forced to switch to lower-paid employment, in order to balance work and caring commitments (Gregory and Connolly, 2008). For the US, England et al (1999) found little evidence to support the view that occupations with disproportionately high shares of female workers had lower pay penalties for intermittent employment, which is consistent with a constrained choice argument.…”
Section: Chapter 1 Introductionsupporting
confidence: 61%
“…There is also a political economy and bureaucracy literature, where public employment is seen as an instrument for politicians to channel rents to specific groups either to generate political support (Gelb, Knight, & Sabot, 1991), to disguise the amount of transfers channelled to some favoured minority group (Alesina, Baquir, & Easterly, 2000), or to create commitment within a bureaucracy (Kessing & Konrad, 2008). 2.…”
Section: Fundingmentioning
confidence: 99%
“…En effet, les responsabilités parentales sont typiquement associées à des caractéristiques particulières -recherche d'un emploi proche du lieu de résidence, absentéisme, interruptions de la carrière et de la formation, refus des promotions -qui sont habituellement associées à une moindre accumulation de capital humain. A cet égard, Connolly et Gregory (2008aet 2008b ont montré que l'écart salarial entre hommes et femmes s'est réduit pour les femmes à plein temps et creusé pour les femmes à temps partiel, ce qui s'explique par le fait que le temps partiel est fortement concentré dans les professions faiblement rémunérées. Plus in-quiétant, selon ces auteurs, on observe une descente le long de l'échelle professionnelle de nombreuses femmes qui travaillent à temps partiel sur des postes faiblement rémunérés, alors qu'auparavant elles occupaient des emplois à plein temps d'un niveau supérieur et mieux rémunérés.…”
Section: Les Femmes Et Le Travail à Temps Partielunclassified